The Stranger - Sarvis, Abby; Hagen, Kate K.; Long, Jessi; Reeder, Caroline; Irwin, Rey (My University, 2016)
Cast: Charile King Hagen, Kate King Hagen, Abby Sarvis, Caroline Reeder, Jessi Long
Citation: GRMN510. (2016). The Stranger. K-State 48 Film Festival, 2016
Keywords: GRMN510; K-State 48 Film Festival